Analisis Penerapan Pembiayaan Murabahah di Lembaga Keuangan Mikro Syariah: Studi Kasus di BMT Kabupaten Situbondo dan Jember - Misbahul Ali; Achmad Achmad (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2018)
Murabaha are the most widely used Syariah financial institution in channeling financing, both banking and non-bank. But in practice there are various forms of application, including is using two contracts at once (murabaha bil wakalah). This form raised the judgment that murabahah 'alleged' practice is similar to ma'dum selling practices and mark-up-based financing as in conventional banks. This paper aimed to determine the levels of BMT Salafiyah Situbondo and BMT NU Jember adherence to the concept of Fiqh and Fatwa DSN-MUI in the application of murabahah financing. In conclusion, that the two BMTs have three alternative forms of murabahah financing in accordance with the concept of Fiqh and Fatwa DSN-MUI, although the way of purchasing goods and deliveries is done directly or indirectly. This compliance is driven by a passion for maintaining the blessing of business revenue earned by BMTs.